(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
This study investigates the complex relationship between science and religion, with a specific focus on Islam and its socio-economic implications in Northern Nigeria. The region, despite Islam's historical legacy of encouraging scientific inquiry, faces significant challenges including poverty, gender-based violence, low healthcare utilization, and educational stagnation, often justified by religious doctrine. Through a systematic literature review and descriptive-analytical research design, this paper assesses whether these harmful practices are rooted in core Islamic teachings or stem from cultural attitudes, ignorance, and misinterpretation. The analysis utilizes Ian Barbour's typology (Conflict, Independence, Dialogue, Integration) to frame the science-religion dynamic. The findings reveal that the prevalent socio-economic setbacks are not due to an inherent conflict between Islam and science. Instead, they are primarily driven by a "folk" interpretation of Islam that syncretizes religious identity with pre-existing cultural norms and a lack of religious and scientific literacy. The study concludes that a multifaceted approach, involving collaboration between religious leaders, educational institutions, and government bodies to promote accurate religious interpretation and scientific awareness, is essential for addressing the root causes of these issues and fostering sustainable development in Northern Nigeria.